Systematic Review: Protective Factors from the Risks of Stunting in Breastfeeding Period - Riris Diana Rachmayanti; Zulfa Kevaladandra; Faisal Ibnu; Nur Khamidah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2022)
Background: Stunting is a chronic nutrition condition marked by improper growth of body height compared to one’s age. One of the factors that affect stunting is exclusive breastfeeding as breast milk contains macronutrients, micronutrients, and bioactive substances to support the growth and development of children under five and act as an anti-infection. Non-optimal breastfeeding causes children to have inadequate nutrition intake and body immunity, which may result in malnutrition and stunting. This study aims to identify the effects of exclusive breastfeeding on the incidence of stunting in children under five.Method: A systematic review was conducted using eight indexed articles with keywords of